Development of a spatially explicit network model of urban metabolism and analysis of the distribution of ecological relationships: case study of Beijing, China. (20th January 2016) - Zhang, Yan; Xia, Linlin; Fath, Brian D.; Yang, Zhifeng; Yin, Xinan; Su, Meirong; Liu, Gengyuan; Li, Yanxian
Abstract: In this paper, we develop a spatially explicit model of carbon transfers between regions of an urban area. The carbon transfers represent the metabolic processes due to regional land use changes. We used the model to identify spatial heterogeneity in the carbon metabolic structure, functions, and relationships within the network. Data for Beijing from 1990, 1995, 2000, 2005, and 2010, were combined with empirical coefficients, to construct the network. We used ecological network analysis to analyze the structure and function of the network, and to determine the ecological relationships between the components of the system, their distribution, and their changes over time. The analysis revealed that carbon throughflow of the network decreased and positive relations mostly outweighed negative relations. Exploitation relationships were the dominant type in Beijing during most of the study period, particularly in the northwest before 2000, but moved towards the southeast over time, leaving competition relationships with losses of benefits dominant in the northwest. Mutualism relationships with mainly beneficial carbon flows were dominant in the southeast, increasing in frequency in this region throughout the study period. The results provide a theoretical basis for planning adjustments to the city's structure to achieve low-carbon goals. Highlights: We built a carbon metabolic network model based on urban spatial heterogeneity. We analyzed variation in the model's structure, functions, and relationships. Negative utilities increased rapidly because of increasing competition. Urban land should become the dominant component to attain metabolic balance.